International Studies in Educational Inequality, Theory and Policy
LXIV, 941 p.
Keywords: Inequality is a marked and persistent feature of education systems, both in the developed and the developing worlds. Major gaps in opportunity and in outcomes have become more critical than in the past, thanks to the knowledge economy and globalization. More and more populations, both rich and poor depend on successful use of school and on gaining post-school qualifications. But access to high-quality schooling, success at school, and chances of higher education all remain socially divided, with implications for economic opportunities, personal growth, and civic and community development. What causes these divisions in how education systems work? Have decades of public investment brought about at least some improvements, even if major gaps remain? If not, what are the barriers, the social processes which have frustrated the efforts of government? The pursuit of equity as a goal of public policy is examined in this book through a series of national case-studies, covering many different global contexts from the wealthiest to some of the poorest nations on earth. What have we learnt from the policy experience globally? Do we know more today than yesterday about the origins of social inequality? Are our policies better framed, better designed to tackle inequality? And which way forward? What does the evidence suggest in terms of future approaches and emphasis? This work is published in three volumes which together form a 3-volume set.